Good Governance, Organizational Culture on Organizational Effectiveness of the Municipalities in the Southern Thailand - เลขะกุล, กิตติ์รวี; สวัสดิ์แก้ว, นิวัตน์; เทพวารินทร์, ศรัญลักษณ์ (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2019)
The purpose of the research was to study the relationship between administration of good governance and organizational culture which affecting on organizational effectiveness of management in terms of the balanced score card of municipalities in southern region of Thailand. 1คณะรัฐศาสตร์ มหาวิทยาลัยหาดใหญ่ 1Faculty of Political Science, Hatyai University This quantitative research used questionnaire as the main research instrument. The 87 municipalities in 14 southern provinces of Thailand were selected as sampling. Based on simple random and multistage random method from 374 of totality. Data was collected by structured questionnaires which were designed according of good governance, organizational culture and organizational effectiveness factors. The key informants were in executive position of municipality, consisting of 87 mayors and 87 municipal clerks of municipalities, giving 174 executives in total. Analysis of data was done by using package program for social research. Multiple regression analysis was used to this study. The results of the research showed that according to multiple regression equation, good governance and organizational culture correlated with the organizational effectiveness of municipalities in southern region of Thailand. It was statistically significant at .001 level. Missionary culture influenced the organizational effectiveness of municipalities in southern region of Thailand with statistical significance of .001. Concerning the good governance principles of management, it affected organizational effectiveness of municipalities in southern region of Thailand at .01 level of significance. All of these factors could explain the organizational effectiveness of municipalities in southern Thailand were 56.80 percent.